STRATEGI GURU DALAM MENGEMBANGKAN KARAKTER MANDIRI ANAK USIA DINI KELOMPOK BERMAIN BUDI MULIA KECAMATAN GALING TAHUN PEMBELAJARAN 2022-2023 - Marini (Samawa (Sakinah, Mawaddah Warahmah), 2023)
The purpose of this research is to reveal how the teachers strategy plans in developing the independent character of this research is to reveal how the teacher’s strategy pllans in developing the independent character of eary childhood in the budi mulia galing play group for the 2022-2023 school year,how to implement the teacher strategy in developing the independent character of the early childhood budi mulia galaing play group for the 2022-2023 academic year. 2023 and ,what are the results of implemnting the independent character of early childhood play group budi mulis galing village academic year 2022-2023 this study uses a qualitative approach and a type of phenomenological research. Data collection techniques using abservation, interviews and documentation.the analysis techniques used are data reduction,data display and data verification and conclusion. The result of the research show that how do teachers’ strategic planning in developing independent character of early childhood play groups budi mulia,tempapan hulu village,Dusun of the 2022-2023 academic year make RPPH,develop independent character according to the guiddebook,how to implement the teacher’s strategy in developing the independent character of early childhood play groups budi mulia galing for the 2022-2023 academic year consists of several steps,namely introduction,core and closing.what are the results of implenting the teacher’s strategy in developing the independent character of implementing the teacher of early childhood play groups budi mulia tempapan hulu village,hamlet for the 2022-2023 academic year developing character is then adjusted to the aspects to be achieved, namely cognitive and moral values.